Conceptualizing the "Corporate Nervous Net": Decentralized Strategic Communication Based on a Digital Reporting Indicator Framework. Issue 5 (20th October 2019) - Knebel, Sebastian; Seele, Peter
ABSTRACT: The digital revolution challenges strategic communication. Artificial Intelligence (AI), Big Data, and the Internet of Things (IoT) create a rapidly changing environment for organizations as well as system complexities. To fulfill its task in ensuring the long-lasting success of organizations' strategic communication needs to continuously adopt to this revolution. This article approaches the question of how strategic communication can adapt to the digitalization. In order to do so, the article conceptualizes the corporate nervous net and a predictive reporting indicator module with real-time feedback loops. As a result, the strategic communication body of knowledge is extended to include digital, assisted, decentralized communication. Decentralized strategic communication proposes a self-organizing, bottom-up approach of strategic communication under the principle of subsidiarity. It keeps complexity at a manageable level and enables the usage of local knowledge and quick adaptation to rapid changes. The proposed resilient approach to strategic communication uses the driving forces of the digital revolution of big data, AI and IoT in its favor instead of trying to control them.